Role of procalcitonin in diagnosis of neonatal sepsis and procalcitonin guided duration of antibiotic therapy - Bharti, Abnish Kumar; Verma, Manoj Kumar; Gupta, Anuj; Mishra, Devendra Kumar (International Journal of Contemporary Pediatrics, 2020)
Background: Neonatal sepsis is one of the important causes of neonatal morbidity and mortality particularly in the developing countries. Accurate and quick diagnosis is difficult because clinical presentation is non-specific, bacterial cultures are time-consuming and other laboratory tests lack sensitivity and specificity. Procalcitonin (PCT) is often reported to be more superior to C-reactive protein (CRP), being more sensitive and specific, starts to rise earlier and returns to normal concentration more rapidly than CRP. Methods: It is a hospital based prospective observational study. Blood samples were obtained and analyzed for blood culture, septic screen including serum CRP and PCT. Neonates were categorized into proven sepsis (n=39), probable sepsis (n=21) and clinical sepsis (n=40) groups on the basis of laboratory findings and risk factors. Data was analyzed by using standard statistical tests using SPSS 16. Results: Out of 100 cases, elevated PCT level >0.5 ng/dl was detected in 75 and >2 ng/dl was detected in 51 whereas CRP was positive only in 61 cases. Among the 39 culture positive cases, elevated serum PCT level was noticed in 39 (100%) cases whereas CRP level was noticed in 30 (76.9%) cases. Mean PCT levels were significantly high according to infection severity (P<0.01). Procalcitonin (sensitivity 87.2%, specificity 72.13%, positive predictive value 66.7% and negative predictive value 89.8% and with p value of <0.001) is more superior than CRP to predict sepsis in neonate. The mean duration of antibiotic therapy was 12.46±4.62 days in definite sepsis, 4.53±1.78 days in probable sepsis group and in clinical sepsis group 3.75±1.33 days by serial PCT measurement. Conclusions: Serum PCT levels >2 ng/dl has got a better sensitivity and NPV, which help us not only in the early diagnosis but also in the prognosis and duration of antibiotic therapy.